Troubleshooting Gait Disturbances in Parkinson’s Disease With Deep Brain Stimulation - Pozzi, Nicoló G.; Palmisano, Chiara; Reich, Martin M.; Capetian, Philip; Pacchetti, Claudio; Volkmann, Jens; Isaias, Ioannis U. (Frontiers in Human Neuroscience, 2022)
Deep brain stimulation (DBS) of the subthalamic nucleus or the globus pallidus is an established treatment for Parkinson’s disease (PD) that yields a marked and lasting improvement of motor symptoms. Yet, DBS benefit on gait disturbances in PD is still debated and can be a source of dissatisfaction and poor quality of life. Gait disturbances in PD encompass a variety of clinical manifestations and rely on different pathophysiological bases. While gait disturbances arising years after DBS surgery can be related to disease progression, early impairment of gait may be secondary to treatable causes and benefits from DBS reprogramming. In this review, we tackle the issue of gait disturbances in PD patients with DBS by discussing their neurophysiological basis, providing a detailed clinical characterization, and proposing a pragmatic programming approach to support their management.